PENGARUH STATUS SOSIAL EKONOMI TERHADAP PARTISIPASI ORANG TUA DALAM PENYELENGGARAAN PAUD DI DESA TELUK PINANG KECAMATAN GAUNG ANAK SERKA KABUPATEN INDRAGIRI HILIR - Nuraini '; Zulkifli N '; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: There is a phenomenon in the mostly elderly people associated with participation in the implementation of early childhood, such as the uneven level of participation of parents in providing support, such as the willingness of parents bear the cost of organizing the PAUD in cash or labor. Parents who have a background in higher education consider that institutions of early childhood education is the beginning of formal education, in contrast to parents who think education is the experience, where parents who think his experience is only complete primary school will assume that the institution of early childhood education is not so important. Parents who do not work (house wives) thought that by teaching children at home alone will suffice. In addition to the parents who have low income believe that early childhood education would be a waste of money. The purpose of this study was to determine the effect of socio-economic status of the parents' involvement in the organization of early childhood in the village of Teluk Pinang Kecamatan Gaung Anak Serka Kabupaten Indragiri Hilir. The study population was 39 parents. The samples are saturated samples so the population sampled as many as 39 people. In this study, the hypothesis is there are significant socio-economic status of the parents' involvement in the organization of early childhood in the village of Teluk Pinang Kecamatan Gaung Anak Serka Kabupaten Indragiri Hilir. It is seen from the results of the chi square test is, if the chi-square calculate ˃ chi square table then there is the influence of social status on parent participation.Keywords: Socio-Economic Status, Participation